1989
DOI: 10.1111/j.1442-9993.1989.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of experimentally disturbed patches by stream macroinvertebrates in the Acheron River, Victoria

Abstract: Twenty-five patches (1 m^) of natural stream substratum in the Acheron River. Victoria, were physically disturbed by kicking and raking during winter 1986 and summer 1987. The macroinvertebrate composition of these disturbed patches was examined at various times over the following 71 days, and compared with adjacent undisturbed control patches sampled concurrently.The disturbance did not alter the particle-size distribution (>150 nm) of the disturbed patches. Organic material was reduced in the disturbed patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 41 publications
5
65
1
Order By: Relevance
“…In contrast, the marked rocks at the class site subjected to OE stream classes experienced more frequent substrate disturbance via student-activity and spates. Significant differences (P < 0.05) in mean macroinvertebrate abundance, mean taxa richness, mean EPT abundance, and mean clinger abundance between the class site subjected to OE stream classes and the unused site at the end of the study are consistent with findings in other studies of anthropogenic disturbance in which disturbance caused a decrease in macroinvertebrate colonization (Clifford 1982;Reice 1985;Robinson and Minshall 1986;Doeg et al 1989;Death 1996;Matthaei et al 1996; Wright and Li 1998; McCabe and Gotelli 2000; Laing 2008;Robinson et al 2011). Thus, our results indicate that the greater frequency of student-induced substrate movement as a result of OE stream classes at the class site suppressed macroinvertebrate colonization of rocks.…”
Section: Macroinvertebrate Colonizationsupporting
confidence: 89%
“…In contrast, the marked rocks at the class site subjected to OE stream classes experienced more frequent substrate disturbance via student-activity and spates. Significant differences (P < 0.05) in mean macroinvertebrate abundance, mean taxa richness, mean EPT abundance, and mean clinger abundance between the class site subjected to OE stream classes and the unused site at the end of the study are consistent with findings in other studies of anthropogenic disturbance in which disturbance caused a decrease in macroinvertebrate colonization (Clifford 1982;Reice 1985;Robinson and Minshall 1986;Doeg et al 1989;Death 1996;Matthaei et al 1996; Wright and Li 1998; McCabe and Gotelli 2000; Laing 2008;Robinson et al 2011). Thus, our results indicate that the greater frequency of student-induced substrate movement as a result of OE stream classes at the class site suppressed macroinvertebrate colonization of rocks.…”
Section: Macroinvertebrate Colonizationsupporting
confidence: 89%
“…However, the post-flood increase in macroinvertebrate abundance was within the values recorded during the pre-flood period. Such resilience studies in temporary streams have been reported previously (e.g., Doeg et al, 1989;Grimm & Fisher, 1989;Lake & Schreiber, 1991). The main factor that may account for the apparent high resilience of the stream macroinvertebrate community was the rapid decrease in discharge from 1515 to 258 l s −1 .…”
Section: Discussionmentioning
confidence: 76%
“…The effect of these hydrological events is one of the principal environmental factors influencing the structure and function of macroinvertebrate communities in Mediterranean streams (Langton & Casas, 1998;Prenda & Gallardo-Mayenco, 1996;Prenda & Gallardo-Mayenco, 1999;Puig et al, 1991;Ubero-Pascal et al, 2000). Another characteristic of these systems is the rapid capacity to recover following these natural disturbances (Boulton et al, 1988;Closs & Lake, 1994;Doeg et al, 1989;Grimm & Fisher, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental studies have explored the length of time for community recovery after disturbance (e.g., Cairns et al 1971;Doeg et al 1989;Death 1996) and a few have assessed the significance of different sources of colonists to this recovery (e.g., Townsend & Hildrew 1976;Williams & Hynes 1976;Williams 1977). However, none has investigated benthic colonisation patterns in North Island, New Zealand gravel bed rivers.…”
Section: Introductionmentioning
confidence: 99%